The chronic care model: congruency and predictors among patients with cardiovascular diseases and chronic obstructive pulmonary disease in the Netherlands - Cramm Jane; Nieboer Anna (BMC, 2012)
Abstract Background The Chronic Care Model (CCM) achieved widespread acceptance and reflects the core elements of patient-centred care in chronic diseases such as CVD and COPD. Our aim is to assess the extent to which current care for CVD and COPD patients aligns with the CCM in Dutch healthcare practices in the early stages of implementing disease-management programmes, thereby revealing possible predictors that tell us whether certain patients are more likely to receive CCM-compliant care than others. Methods We use a cross-sectional study, addressing CVD or COPD patients from 106 primary care practices in the Netherlands. Our response rate was 53%; i.e., 2,487 of 4,681 questionnaires were returned. The Patient Assessment of Chronic Illness Care (PACIC) was used to assess compliance with CCM. Quality of life was assessed with the Short-Form 36 Health Survey (SF-36) and we used the Hospital Anxiety and Depression Scale (HADS) to assess depressive symptoms. Multilevel regression models were performed to reveal predictors of high CCM compliance. Results With a mean (SD) of 2.77 (0.86) in CVD patients and 2.89 (0.89) in COPD patients (p = 0.002), the PACIC sum score was lower than in previous studies conducted in HMOs in the US, but similar to a European primary care setting study. The PACIC score was associated with age and depressive symptoms in both patient groups. Conclusions Younger and less depressed patients report higher PACIC scores, indicating that their care better aligns to the CCM.